Strategi Manajemen Hubungan Masyarakat di MTs Nurul Athfal Ulujami Kabupaten Pemalang - Subhan, Fajar; Untung, Slamet (Jurnal Ilmu Pendidikan Muhammadiyah Kramat Jati, 2025)
Public relations management in education is a series of activities aimed at building and maintaining good relationships between educational institutions and various interested parties, such as students, parents, teachers, staff, alumni, community and government. This research aims to analyze the public relations management strategy at MTs Nurul Athfal Ulujami, Pemalang Regency. The type of research used in this study is field research with a qualitative approach. The research results show that community relations at MTs Nurul Athfal are carried out through various techniques and approaches that are adapted to the conditions of the surrounding community. Public relations activities involve direct communication, such as meetings and consultations, as well as indirect communication through social media, brochures and banners. The application of various public relations techniques, whether in words, actions or in combination, supports the establishment of harmonious relationships between madrasas, students, parents and the community.